Smart Book Media Education on Preventing Dental Caries - Prahara, Fulvia Rimba; Laela, Dewi Sodja; Nurnaningsih, Hera; Putri, Megananda Hiranya; Heriyanto, Yonan; Nurjanah, Neneng (Center of Excellent (Pusat Unggulan Iptek), 2024)
Dental caries problems are experienced by most elementary school children in Indonesia. Lack of children's knowledge about preventing dental caries affects their behavior in maintaining dental and oral health. Efforts to prevent dental caries can be done by providing dental and oral health education to children through learning media aids, namely smart books. The purpose of the study was to see the effect of smart book media education on preventing dental caries in elementary school students. The type of research used was pre-experiment with a One Group Pre-Test Post-Test Design. The sample was taken by random sampling, the sample size was based on the Isaac and Michael formula with an error rate of 5% and 37 elementary school students in grade 5 were obtained. The variables in the study were smart books and dental caries prevention. Smart book media has been tested and declared feasible by media experts and material experts. Hypothesis testing using Wilcoxon Sign Rank. The results of the study showed an increase in caries prevention behavior in all students (100%) from the aspects of Knowledge, Attitude and Action after being given education through smart books. Wilcoxon Sign Rank analysis showed that there was a significant influence of the results of smart book education on dental caries prevention behavior in the aspects of Knowledge, Attitude, and Action 0.001 (p < 0.05). The use of smart books as an educational medium has been proven to be able to increase dental caries prevention behavior effectively in elementary school children. Elementary school students become more aware of the efforts that must be made to prevent caries